Correspondence between theory and methodology: a case study of accounting for the environment in organisational research - Indra Abeysekera (Environmental Research Communications, 2023)
The two most widely investigated environmental domains concerning firms are environmental disclosure and environmental performance. This study examines how well operational variables inform constructs in these two domains. The empirical research process has two aspects: truth making and truth building. Truth making using operational variables must align with truth building with respect to constructs. Towards this aim, this article explores two research questions. First, are disclosure and performance operationally and conceptually different? Second, do the operationalised and conceptualised variables have a strong association in each domain—disclosure and performance? This study uses research data matrices available from a published journal article as an example to demonstrate analytical details. It uses the canonical correlation analysis research method for analysing matrix data to answer the research questions. The findings show that disclosure and performance are conceptually different domains. However, results show that operational variables associate differently with the construct. The findings show that selecting variables in empirical settings that reflect constructs can correspond with theoretical advancements.